Development Of Web-Based English Learning Media Using Content Management System (Word Press) And Elementor Plugin - Farmana, Yuditra; Yasin, Muhammad (CV. Inara in Colaboration with www.stie-sampit.ac.id, 2022)
This research was conducted based on the importance of English learning media that can be accessed by everyone anytime and anywhere, in this case not limited to the students of STIE Enam Enam Kendari butstudents from other tertiary institutions andeven the general public. It is related to the Ministry of Education,Cultures, Researchand Technology’s program about Freedom to Learn (Merdeka Belajar Kampus Merdeka)which creates a flexible and innovative teaching-learning process. Therefore this research aims to design and develop website-based learning media using a content management system (CMS), namely WordPress and the elementor plugin for English courses at STIE Enam Enam Kendari. The stage of research method used is a